Identifikasi Genetik Ikan Nilem dengan Pendekatan DNA Barcoding - Dailami, Muhammad; Yuniarti, Ating; Widodo, Maheno Sri; Pratama, Rakhmad Ndaru; Ariyani, Destia Fitri; Siahaan, Marthin Daniel Theo Gratia; Maulana, Antajala Rian; Ramadhan, Surya Dewa; Putri, Radwa Fathin H; Nurcahyani, Shinta Eka; Milansari, Sindi; Mayor, Corazon Ell Merilia Papuani (Penerbit Brainy Bee, 2025)
Nilem fish (Osteochilus vittatus) is a species of freshwater fish from the Cyprinidae family which has ecological and economic importance in Indonesia, with its natural habitat in rivers, swamps and stagnant waters. Accurate species identification is very important in biological research and fisheries resource management, but morphological identification methods have several limitations. DNA barcoding is a revolutionary molecular technique that uses short DNA sequences to identify and differentiate species with high accuracy. The use of DNA barcoding in identifying freshwater fish in Indonesia has shown significant development, including in a comprehensive study documenting 1,172 native freshwater fish species. The research